Pengembangan Aplikasi Watermark Digital pada Unit Records Center Sekretariat TVRI Sumatera Selatan - Denita, Nayra Alya; Pratama, Dicky (MDP Student Conference, 2025)
TVRI South Sumatra is a regional television station established by Televisi Republik Indonesia for the South Sumatra Province. In addition to producing broadcast content, TVRI South Sumatra also manages various important documents related to archives. The documents are scanned into digital form, making them vulnerable to forgery and misuse if not properly protected. Currently, securing digital documents is done using Adobe Photoshop, which can take a long time due to the process of adjusting the position, size, and transparency level of the watermark, especially if the document has many pages. One solution to reduce the time required is to develop a digital watermark application. The purpose of developing a digital watermark application is to simplify the process of adding watermarks to scanned documents in PDF format. The method used in software development is the Rational Unified Process (RUP) method. It can be concluded that the results of the development of the digital watermark application show that this application can automatically add the TVRI South Sumatra logo watermark to documents. This application simplifies the process of providing authentic marks to documents without having to do it manually. Thus, this application can speed up the work process so that it becomes more practical.